Biodiversity and potential functionality of biofilm-sediment biotope in La Muerte lagoon, Monegros Desert, Spain - Berlanga, Mercedes; Picart, Pere; Blasco, Arnau; Benaiges-Fernandez, Robert; Guerrero, Ricardo; Butturini, Andrea; Urmeneta, Jordi (Frontiers in Ecology and Evolution, 2024)
La Muerte lagoon is an ephemeral endorheic water body located in the Monegros desert, Zaragoza, Spain. Amplicon sequencing of the 16S rRNA gene was performed to analyze the bacterial and archaeal communities in biofilm-sediment samples over three years, to understand the dynamic changes in the microbial community. PICRUSt and shotgun metagenomics were used to examine energy production and carbohydrate metabolism pathways. The dominant bacterial phyla were Actinobacteriota, Bacteroidota, Cyanobacteriota, and Pseudomonadota, while Halobacteriota was the predominant archaeal phylum. Despite seasonal environmental fluctuations, the biofilm community remained stable over time, suggesting resilience. The Calvin-Benson cycle was the main carbon fixation pathway, carried out by Cyanobacteria and purple non-sulfur bacteria. Nitrogen fixation by diazotrophs supplied an important nitrogen source. Organic carbon was derived primarily from autotrophs, with little use of allochthonous plant material. The comparison of biofilm-sediment and water column biotopes showed distinct but related prokaryote communities. Biofilm-sediments showed higher taxonomic diversity and different proportions of microbial phyla compared to the water column. This study provides initial insights into the complex microbial life in endorheic lagoons and underscores the importance of protecting these globally threatened habitats. The limited sample size in this study warrants further investigation with a more comprehensive sampling strategy to fully characterize the microbial communities and their functional roles in the different biotopes of La Muerte lagoon.